2005
DOI: 10.2298/zmspn0519081d
|View full text |Cite
|
Sign up to set email alerts
|

Xerotolerant mycopopulations and mycotoxins in muesli components

Abstract: The presence of fungi was investigated in 22 samples of different dried plant origin products used for the preparation of muesli (grain products, dried fruit, nuts, oilseeds), using three media. The determined contamination levels were between 0,6% (grain products) and 46,4% (raisins). The xerotolerant Aspergillus, Penicillium and Eurotium species, mostly toxigenic and fungi from Rhizopus genera, were the most frequent in the investigated samples. Aflatoxin B1 (AB1) was not detected in any sample, while aflato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
0
4
0
2
Order By: Relevance
“…In Serbia, mould contamination of tree nuts was also reported previously. Dimić et al (2005) reported that 17% of analyzed almond samples were contaminated with moulds, while contamination of hazelnuts was negligible. In almond and hazelnut samples were identified Aspergillus, Penicillium and Eurotium species as well as Paecilomyces variotii.…”
Section: Resultsmentioning
confidence: 99%
“…In Serbia, mould contamination of tree nuts was also reported previously. Dimić et al (2005) reported that 17% of analyzed almond samples were contaminated with moulds, while contamination of hazelnuts was negligible. In almond and hazelnut samples were identified Aspergillus, Penicillium and Eurotium species as well as Paecilomyces variotii.…”
Section: Resultsmentioning
confidence: 99%
“…Both species are common contaminant of agricultural products and contamination can occur during pre-harvest, processing and handling (Perrone et al, 2007). Aspergillus niger and A. flavus were also among the most common species isolated from muesli component (Dimic et al, 2005), some dried fruits in Yemen (Alghalibi and Shater, 2004), and dried figs in Iran (Javanmard, 2010). Similar with Aspergillus, two species of Penicillium were also isolated from dates, kiwi and raisins.…”
Section: Resultsmentioning
confidence: 99%
“…Marin et al (2002) reported that P. corylophilum was one of fungal spoilage of bakery products. Penicillium glabrum is also often encountered in food and indoor environment, and has been recovered from fruits, nuts, frozen cakes (Samson et al, 2010) as well as from muesli components (Dimic et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Vrste rodova Penicillium, Aspergillus i Eurotium su takozvane "skladišne gljive" koje se razvijaju na začinima [11], sušenom voću i povrću [23] i sličnim proizvodima (pr. kafa, kakao, seme susama i suncokreta, musli) [24][25][26][27][28].…”
Section: Uv Odunclassified